Estudio de las implicaciones en la modalidad híbrida “distancia-virtual” en directivos de la ESPAM MFL, durante la pandemia COVID-19 - Quijije Intriago, Rosa María (2022)
This is a study of the implications in the hybrid modality "Distance - virtual" in executives at the ESPAM MFL, during the COVID-19 pandemic, with the purpose of strengthening the training subsystem of the institution. Inductive, deductive, analytical-synthetic, and Delphi methods were used. Among the instruments used: interview guide, SWOT matrix, Ishikawa diagram, brainstorming, all this to solve the variables "hybrid mode" and "implications for managers." It was found through the application of research techniques such as interviews and surveys, that the Higher Education Institution has perfected tactics: a contingency plan for the development of academic activities, training, academic tutorials, implementation and use of technological platforms, a set of guidelines in accordance with national regulations. The effects of the hybrid study modality were identified through a SWOT matrix, determining strengths such as the consolidation of knowledge on the use of techniques, tools and technological resources, among the opportunities the implementation of internationalization processes is reflected, in terms of the weaknesses, there was difficulty in the processes of control, evaluation and monitoring of the teaching work and the threats, where it was detected the lack of budget of the IES. The Cause - Effect diagram helped to know the causes and sub-causes that affect the phenomenon under study; with these results, the action plan was carried out to strengthen technological resources; managers / teachers; students; academic programs, and educational institutions and therefore the quality of the training subsystem.